A paramedian approach for dorsal root ganglion stimulation placement developed to limit lead migration and fracture. Issue 8 (19th August 2021) - Chapman, Kenneth B.; Spiegel, Matthew A.; Dickerson, David M.; Billet, Bart; Patel, Kiran V.; Hunter, Corey; Antony, Ajay; van Helmond, Noud; Deer, Timothy; Kallewaard, Jan Willem; Hagedorn, Jonathan M.; Yang, Ajax
Abstract: Introduction: Dorsal root ganglion stimulation (DRG‐S), has demonstrated superiority in the treatment of complex regional pain syndrome and causalgia. Lead migration and fracture impact DRG‐S therapeutic stability. Lead anchoring reduces DRG‐S lead migration without increasing lead fracture. Lead fracture may be related to lead entrapment in the superficial fascial plane. A novel medialized approach for lead placement and anchoring is presented to address these issues. Methods: We suggest an alternative technique for implanting percutaneous DRG‐S leads at the T10‐L5 levels. Results: A novel medialized ipsilateral technique for lead placement and anchoring for single, bilateral, and adjacent segment placement is presented. The Tuohy needle puncture site is medial to the pedicle and adjacent to the spinous process, two vertebral levels caudad to the target foramen. Trajectory is maintained in the sagittal plane, to access the caudad interlaminar space near the midline. This technique allows for ipsilateral or contralateral lead placement. After epidural access, the introducer sheath is rotated toward the targeted foramen and advanced. The guidewire followed by the lead is passed, and once lead position is confirmed, tension "S" loops are created, followed by anchoring to the deep fascia. Conclusion: We describe a new paramedian technique for DRG‐S lead placement. We propose it will decrease DRG‐S complication rates through anchoring to reduce migration and by avoiding the fascial planes thought to be responsible for fracture. Long‐term outcomes applying our proposed techniques are required for determining the true impact, however, early anecdotal results suggest that these new techniques are favorable.